2015
DOI: 10.3390/ijms160510457
|View full text |Cite
|
Sign up to set email alerts
|

4,4'-Diisothiocyanostilbene-2,2'-disulfonic Acid (DIDS) Ameliorates Ischemia-Hypoxia-Induced White Matter Damage in Neonatal Rats through Inhibition of the Voltage-Gated Chloride Channel ClC-2

Abstract: Chronic cerebral hypoperfusion is believed to cause white matter lesions (WMLs), leading to cognitive impairment. Previous studies have shown that inflammation and apoptosis of oligodendrocytes (OLs) are involved in the pathogenesis of WMLs, but effective treatments have not been studied. In this study, 4,4'-diisothiocyanostilbene-2,2'-disulfonic acid (DIDS), a chloride (Cl−) channel blocker, was injected into chronic cerebral ischemia-hypoxia rat models at different time points. Our results showed that DIDS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…This process usually occurs in the third trimester of pregnancy and even last after birth 9 . Numerous studies have shown that during the period when OPCs differentiate into early OLs, immature OLs were vulnerable to injury factors, such as hypoxia-ischemia 10 , toxicity 11 , oxidative stress 12 etc. which led to OPCs/Pre-OLs injury and myelination disturbance 13 .…”
Section: Introductionmentioning
confidence: 99%
“…This process usually occurs in the third trimester of pregnancy and even last after birth 9 . Numerous studies have shown that during the period when OPCs differentiate into early OLs, immature OLs were vulnerable to injury factors, such as hypoxia-ischemia 10 , toxicity 11 , oxidative stress 12 etc. which led to OPCs/Pre-OLs injury and myelination disturbance 13 .…”
Section: Introductionmentioning
confidence: 99%
“…2) A criti-cal reduction of blood flow to a region of the brain such as an acute obstruction of an artery causes ischemia, which elevates levels of free radicals, extracellular glutamate and intracellular calcium, resulting in inflammation, neurologic malfunctions and neuronal cell death. 30) DIDS significantly downgraded the level of reactive oxygen species in chronic cerebral ischemiahypoxia rat models. 31) Even if DIDS itself upregulates neuronal cell death locally, it is likely to inhibit the expansion of death signals between cells in the ischemic penumbra broadly, leading to the putative benefit.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, we have reported that 15d-PGJ 2 inhibited the phosphoinositide 3-kinase (PI3K)-Akt pathway, resulting in the neuronal apoptosis. 32,33) 15d-PGJ 2 is not only one of neurodegenerative mediators 30) but also one of endogenous anticancer agents. 34) The cytotoxicity of 15d-PGJ 2 was potentiated by the combination with other pharmaceutical agents in renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the excessive activation of CLC-2 may lead to cell damage. A report concerning the white matter of neonatal rats demonstrated that ischemia-hypoxia elevated the activation of CLC-2 and subsequently initiated apoptosis in OLs ( 23 ). He et al ( 36 ) reported that, in the white matter of newborn rats that presented with gestational diabetes mellitus, activation of CLC-2 resulted in apoptosis and myelination inhibition via repression of the phosphatidylinositol 3-kinase-protein kinase B signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Ca 2+ transients are considerably larger in mature OLs compared with OPCs, indicating that Ca 2+ may be a signal for the initiation of myelin formation ( 22 ). The inhibition of voltage-gated chloride channel (CLC)-2, by 4,4′-diisothiocyanostilbene-2,2′-disulfonic acid (DIDS), is able to protect developing OLs in the white matter following ischemia-hypoxia injury in neonatal rats ( 23 ). However, the function of CLC-2 on OPC differentiation and myelination is not fully understood.…”
Section: Introductionmentioning
confidence: 99%